1996
DOI: 10.1093/rheumatology/35.7.660
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Spondylodiscttis in Ankylosing Spondylitis—a Controlled Study

Abstract: (1) spondylodiscitis occurs in approximately 8% of patients with AS; (2) these patients have early onset of disease; (3) multiple-level lesions in the spine are not uncommon among those with spondylodiscitis; (4) lesions are usually asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
3
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 7 publications
1
27
3
4
Order By: Relevance
“…Nevertheless, AL often involves only a single level, indicating that additional factors could be involved [14]. An infectious origin has also been suggested because of the radiographic resemblance to spondylodiscitis [15,16], but this has never gained much popularity in literature. Regardless of the exact etiology, a final common pathway exists, in which mechanical stresses prevent the lesion from fusion and the development of pseudarthrosis ensues [1].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, AL often involves only a single level, indicating that additional factors could be involved [14]. An infectious origin has also been suggested because of the radiographic resemblance to spondylodiscitis [15,16], but this has never gained much popularity in literature. Regardless of the exact etiology, a final common pathway exists, in which mechanical stresses prevent the lesion from fusion and the development of pseudarthrosis ensues [1].…”
Section: Discussionmentioning
confidence: 99%
“…Even though in AS some Authors reported a frequency of discovertebral erosions in a range of 1.5-28% (22,23), in EA our research group has recently found a high prevalence of this lesion (30.55%), confirming that they are an important characteristic aspect of all SpA. In particular, we found a high prevalence in patients with axial and peripheral subset (31.82%), suggesting that spondylodiscitis could be a characterizing feature of the overlap subset, type 3 axial and peripheral forms (16).…”
Section: Articular Manifestationsmentioning
confidence: 98%
“…5). Solche Veränderungen kommen in weniger als 10% der Patienten mit AS vor [24]. In der MRT-STIR-Sequenz zeigen sie sich als hyperintenses Signal in der Bandscheibe und in entweder einem oder beiden angrenzenden Wirbelkörpern.…”
Section: Spondylodiszitisunclassified